Noteworthy bird records at Lagoa Santa, southeastern Brazil - Rodrigues,Marcos (2008)
Lagoa Santa, a small town in southeastern Brazil where naturalist Peter Lund lived, is regarded nowadays as an important historical site for the biological sciences. From 1847 to 1855, J.T. Reinhardt, hosted by Lund, collected 343 bird species. This material is an outstanding reference for many modern ornithological studies. The present paper reports the occurrence of some rare and threatened birds for the region of Lagoa Santa between 1998 and 2005. In this account I list the Rusty-margined Guan Penelope superciliaris Temminck, 1815; the Roseate Spoonbill Platalea ajaja Linnaeus, 1758; the Maguari Stork Ciconia maguari (Gmelin, 1789); the Wood Stork Mycteria americana Linnaeus, 1758; the Black Hawk-eagle Spizaetus tyrannus (Wied, 1820) and the Turquoise-fronted Parrot Amazona aestiva (Linnaeus, 1758). It is also reported the southernmost record for the Blue-and-yellow Macaw Ara ararauna (Linnaeus, 1758) and the range extension of the Crowned Slaty flycatcher Griseotyrannus aurantioatrocristatus (d'Orbigny and Lafresnaye, 1837). These data can be used as a baseline for studies of colonization and extinction.